La day surgery centralizzata: l’appropriatezza clinica e organizzativa come leva di creazione di valore sanitario - Vogliolo, Bruno; Nieddu, Salvatore; Bianco, Maurizio (Farmeconomia. Health Economics and Therapeutic Pathways, 2001)
In the last years Public Health Service has been trying to find out solutions in order to improve its health value added creation capacity. The implementation of the Day-surgery division mainly aims to follow that direction, since it enables the improvement of the ratio between efficacy, quality and healthcare suitability and on the other hand efficiency, costs and modality of better resources utilization. The centralization of Day-surgery activities proposes some innovative characteristics, concerning that it introduces an organizational model focused on needs and it performs the separation of the clinic and therapeutic activities from the ones involving the assistance. Both economic and qualitative advantages deriving from the changes stand out in term of: - high possibility of activities’ scheduling; - improved customer satisfaction; - rationalisation of day-hospital recovery, with positive effects on the inpatients; - improved hospital economic stability. This study was carried out with the support of the multiple-skill group composed of doctors, nurses, administrative staff as well as experts in the field of organisation with an aim to provide the full outline of the necessary competences. The proposed discussion reflects the multidisciplinary view of the problem and different perspectives. Each of them regards particular aspects and implications indicated as following: - clinical perspective, related to the possibility of day-surgery interventions both from the medical and the anaesthetic point of view; - organisational perspective, which refers to the possible day-surgery models in conjunction with the organisational model and their peculiarities; - operative perspective, which consist of the analysis of the ideal structural dimension, flows of activities among all services involved and the analysis of the productive capability; (number of necessary beds, staff dimension and a relapse of the operation activities needs); - economic perspective, focused mainly to provide the final valuation on the capacity of the project to contribute to the improvement of the hospital.